Enhancing farm income and livelihood security through water management and crop diversification - Sethi, Debabrata; Mishra, Sumanta Kumar; Nanda, Prabhakar; Thakur, Amod Kumar; Sahoo, Isha Anindita; Mahanta, Sivaprasad (Indian Farming, 2025)
This success story highlights the transformative impact of Farmer FIRST Programme (FFP) of the ICAR-Indian Institute of Water Management on Smt Gitanjali Naik, a tribal farm woman from Keonjhar district, Odisha. Initially facing challenges such as low crop productivity, poor irrigation facilities, and a lack of crop diversification, Smt Naik's life changed drastically through the adoption of scientific water management, crop diversification, and modern farming techniques. By implementing practices like hybrid rice cultivation, vegetable farming with drip irrigation, mulching, and the rearing of livestock, she increased her annual income from `19,000-24,000 to `6,08,300 in just seven years. Her success has turned her into a role model for other farmers, and she has earned recognition, including the ‘Best Farmwoman Award’ in 2022. Her story underscores the potential of agricultural innovations to empower farmers, especially women, in tribal areas.